(3Cef GdOhdI aj GdfXGe GdbGfhfj ddghGA hddaVGA GdNGQLj (B/s - (3Ydj UGOb YHO GdMejO UGObs (1979)
(3jJUOQ gPg GdQSGdI aUd JegjOi ddebUhO HGUWdGM GdGef heaghe GUWdGM GdLGShSjg hehbYgG ef GdGUWdGMGJ GdeTGHgg cGdeNGHQGJ hGdeYdheGJ Ke JfbSe GdOQGSI Gdi KdGKI GHhGH NUU GdGhd efgG dOQGSI YhGed GdGef ai GdJfXje GdbGfhfi ddghGA eY TQM GgejI gPG GdYGed hJCKjQg Ydi GdJfXje GdbGfhfi ddghGA hGdeMGhdGJ GdGhdi dGSJNOGe GdghGA ai GdJLSS MJi fgGjI GdMQH GdYGdejg GdGhdi hQOhO aYd Gdabg GdOhdi hGdOhd GdeYfjg MjGd Pdc ceG jYQV gPG GdHGH TQMG dYGed GdGef ai GdeYGgOGJ GdLeGYjI GdefXeg ddghGA Ke dJaGUjd eMGhdI GSJNOGe GdghGA ddMUhd Ydi GdeYdheGJ HYO GdMQH GdYGdejg GdKGfjg hQOhO aYd GdOhd JLGggG ai eMGhdI dJMOjO GdbGYOI GdbGfhfjg GdOhdjg GdJi CNP HgG GdeLJeY GdOhdi ddJYGed eY GdLGShSjg ef GdghGA GeG GdHGH GdKGfi abO NUU dOQGSI YGed GdGef ai GdfXGe GdbVGFi ddbVGA GdNGQLi eY TQM HYV eXGgQ GSJNOGe GdaVGA GdNGQLi ddMUhd Ydi GdeYdheGJ hGdeTQhYGJ GdGeQjcjg hGdShajJjg ai gPG GdeLGd hcPdc TQM GgejI YGed GdGef hJCKjQ GdLGShSjg Ydjg hGdNdGa Mhd eagheg Hjf GdhdGjGJ GdeJMOg GdGeQjcjg hHYV GdOhd GdZQHjg ef Lgg hGdGJMGO GdShajJi hHGbi GdOhd GdTQbjg ef Lgg GNQi heG GOi Gdjg gPG GdNdGa ef YOe GecGf GdJhUd Gdi GdfU Ydi bjhO eMOOI hGVMg Ydi MQjI GdaVGA GdNGQLi ai eYGgOI GdaVGA (B1967 (3Gh Ydi GjLGO MOhO eYjfg Hjf GdghGA hGdaVGA GdNGQLi GeG GdHGH GdKGdK ajJfGhd GdhVY GdbGfhfi GdOhdi ddLGShSjg ef GdghGA hGdaVGA GdNGQLi hGSJJHY Pdc GdJYQV dTQM bhGYO GdbGfhfjg GdOhdjg ddJLSS ai GdMQH HGYJHGQgG GdbhGYO GdbGfhfjg GdOhdjg GdhMjOg GdefUhU YdjgG ai eYGgOGJ Ohdjg GdJi JYQVJ deKd gPG GdehVhY ceG jJYQV gPG GdHGH HGdTQM ddbhGYO GdbGfhfjg GdOhdjg ddLGShSjg ai GdSdGe hehbY GdLGShSjg ai GdSdGe hehbY GdLGShSjg ai GdbGfhf GdOhdi Ke jfJbd GdHGH HYO Pdc dHMK ehVhY GdLGShSjg ef GdghGA ajKHJ hLhO bGYOI bGfhfjI Ohdjg JfU Ydi YOe eTQhYjI gPG GdJLSS hhLhH GeJOGO gPg GdbGYOI GdYQajI Gdi GdbVGA GdNGQLi hCNjQG jJYQV GdHGH HGdTQM deMGhdGJ JHQjQ GdLGShSjg ef GdghGA hGdaVGA GdNGQLi hYOe JCKjQ Pdc Ydi GdhVY GdbGfhfi GdOhdi dgG Ke JYQV GdNGJeg GdfJGFL GdJi Je GdJhUd GdjgG hGdMd GdebJQM ddJZdH Ydi GdNdGa Mhd OhQ GdLGShSjg ai JCejf GdOhd hGdeJeKd ai GfTGA hcGdI Ohdjg eJNUUg ddMUhd Ydi GdeYdheGJ HGdJhGHY GdefGYjg dUGdM GdHTQjg LeYGA(B.s
(3CWQhMI (B((3OcJhQGg(B) . (3LGeYI GdbGgQI (B. (3cdjI GdMbhb (B. (3bSe GdbGfhf GdOhdj GdYGe(B.s
Keywords: (3bGfhf GdWhGQF s -- (3eUQs; (3GdCef Gdbhej s -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdeMGce GdYScQjI s -- (3eUQs